x^2+y^2-2x+6y+10=0,3x+7/3y的值
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 17:54:04
x^2+y^2-2x+6y+10=0,3x+7/3y的值x^2+y^2-2x+6y+10=0,3x+7/3y的值x^2+y^2-2x+6y+10=0,3x+7/3y的值x²+y²-
x^2+y^2-2x+6y+10=0,3x+7/3y的值
x^2+y^2-2x+6y+10=0,3x+7/3y的值
x^2+y^2-2x+6y+10=0,3x+7/3y的值
x²+y²-2x+6y+10=0
(x²-2x+1)+(y²+6y+9)=0
(x-1)²+(y+3)²=0
x-1=0,y+3=0
x=1,y=-3
(3x+7)/3y
=(3×1+7)/(3×3)
=10/9
明白请采纳,
有新问题请求助,
x^2+4y^2-6x+4y+10=0,求x^4-y^4/(x+2y)(x-2y)*x+2y/xy^2+y^3除以(x^2+y^2/y)^2的值
【2(x-y)^3-8(x-y)^2(x+y)+6y(x-y)^2】/2(x-y)^2=
x-y/x-x+y/y-(x+y)(x-y)/y² y/x=2
x²-2x+y²+6y+10=0,求—9(x+y)²+(3x-2y)(2y+3x)的值
x+y/2+x-y/6=5 2(x+y)-3(x-y)=-2
(x+y)/2- x-y/2=6 3(x+y)=4(x-y)
x+y/3+x-y/2=6 4(x+y)-2(x-y)=40
x+y/2+x-y/3=6,4(x+y)-3(x-y)=-20
{(x+y)/2+(x-y)/3=6 4(x+y)-3(x-y)=-20
4(x+y)-3(x-y)=-20,2/x+y+3/x-y=6
x,y 满足x(x-2)-y(y-6)=-10,求x,y的值
{4x-3y-10=0 3x-2y=0,{3x-4(x-y)=2 2x-3y=1,{2(x+y)-(x-y)=3 (x+y)-2(x-y)=1
2(x+y)-3(x-y)=1 6(x+y)+(x-y)=51
{3(x+y)-4(x-y)=4 {x+y/2 + x-y/6=1
6(x-y)-2(x+y)=14 3(x-y)+(x+y)=5
若(x-y)/(x+y)=3 则(x+2y)/(6x-7y)等于
已知X,Y,满足(X+3Y)(X-3Y)=-10(Y^2-6/5)和2X(Y-1)+4(1/2X-1)=0 (X+Y)^2 X^2Y+XY^2注:*/* 是分数
若x-y不等于0,2x-3y=0,则分式(10x-11y)/(x-y)的值是()?(10x-11y)/(x-y) =[(8x-8y)+(2x-3y)]/(x-y) =8为什么8X-8Y=8?(10x-11y)/(x-y)=[(8x-8y)+(2x-3y)]/(x-y)=8+(2x-3y)]/(x-y)=8+0=8